Responsabilidade tributária dos sócios e dirigentes de pessoas jurídicas - Caribé, Luciano Brito (2009)
This work aims at a scientific approach towards the scope and framing of sections 134 and 135 of the Brazilian Tax Code, as well as the other rules related to the limits of fiscal responsibility to partners and executive officers of legal entities, a very relevant subject in the relations between the tax authority and taxpayers. This topic is very important, as we can observe the usage of the patrimonial separation of the legal entity by malicious entrepreneurs as a way to flee from tax payments. On the other hand, the abuses committed by the tax authority are clearly shown, as it has been directly suing partners and executive officers without any regard to the principles and prescriptions of our National Tax System. Our conclusions point towards the need of a stronger rigorousness by the tax authority in attributing tax responsibility to partners and executive officers of corporations. And this attribution must be done in administrative proceedings, where the imposition is formed